Development of Interactive Learning Media Based on Smart Apps Creator for Narrative Text Writing in Fourth-Grade Elementary School - widya cantika; ari suriani; adrias; inggria kharisma; m habibi (Journal of Education and Teaching Learning, 2026)
This research was motivated by the limited use of interactive learning media in narrative writing lessons at elementary schools, causing students to experience difficulties in developing ideas and organizing stories. This study aimed to develop an interactive learning media based on Smart Apps Creator that is valid, practical, and effective for teaching narrative text writing in fourth grade elementary school. This study employed a Research and Development (R&D) method using the Plomp model, which consisted of preliminary research, development or prototyping phase, and assessment phase. The research was conducted at SDN 30 Cengkeh, SDN 14 Koto Lalang, and SDN 05 Kapalo Koto. The research instruments included validation sheets, practicality questionnaires, and learning outcome tests. The results showed that the media obtained 92% material validity, 96% media validity, and 96% language validity, categorized as very valid. The practicality results indicated very practical criteria, with percentages of 88,67% in the one-to-one evaluation, 89% in the small group evaluation, and teacher and student practicality results in each school categorized as very practical. The effectiveness results based on the N-Gain scores showed a moderate or fairly effective category. Therefore, the interactive learning media based on Smart Apps Creator was declared valid, practical, and effective for teaching narrative text writing in fourth grade elementary school.